PERKEMBANGAN POST-LARVA IKAN NILEM Osteochilus hasselti C.V. DENGAN POLA PEMBERIAN PAKAN BERBEDA - Didi Humaedi Yusuf; Gratiana E Wijayanti; Sugiharto Sugiharto (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
Failure of adaptation in feed utilization can result in larval mortality. Post-larval stage is a critical period of fish development in which transition from internal feeding to external feeding occurs. This study aimed to determine the growth and survival of hard-lipped barb (Osteochilus hasselti C.V.) post-larvae fed with different feeding patterns. The experiment was conducted on an experimental basis with a completely randomized design (CRD). The treatments consisted of (P1) 100% Spirulina sp., (P2) 75% Spirulina sp. + 25% pellet powder, (P3) 50% Spirulina sp. + 50% powder pellet, (P4) 25% +75% sp Spirulina pellet powder, and (P5) 100% powder pellets. Day 1 post-hatching larvae were reared in aquaria with density of 17 fish / L for 8 weeks. The larvae were fed as much as 5% of the total weight of biomass. Post-larval development was evaluated by observing the development of the larvae morphology, the body length (every week), the biomass weight (every 2 weeks), and calculating their survival rate at week 8. Morphological data were analyzed descriptively. Data on body length, biomass weight and survival were analyzed using two-way ANOVA followed by LSD test. The results showed that the feeding pattern significantly affected the development of post-larvae (p<0.05). The most advance post-larval development was obtained from the post-larvae fed with 100% pellet powder. In this group, morphological characters of post-larvae in the first week were the mouth start opening, the skin was pigmented, and gall bladder in bi-lobes shaped, caudal fin and dorsal fins were differentiated. Completion of fins development was achieved by the third week when the post-larvae have adult morphological character. The highest body length and biomass weight of the post-larvae was obtained in the group fed with100% of pellets and the highest survival rate was found in the group fed with combination of 50% Spirulina sp. + 50% pellet powder (P3).